2015
DOI: 10.1093/pcp/pcv052
|View full text |Cite
|
Sign up to set email alerts
|

Cucumis sativusL.WAX2Plays a Pivotal Role in Wax Biosynthesis, Influencing Pollen Fertility and Plant Biotic and Abiotic Stress Responses

Abstract: Cuticular waxes play an important part in protecting plant aerial organs from biotic and abiotic stresses. In previous studies, the biosynthetic pathway of cuticular waxes and relative functional genes has been researched and understood; however, little is known in cucumber (Cucumis sativus L.). In this study, we cloned and characterized an AtWAX2 homolog, CsWAX2, in cucumber and found that it is highly expressed in the epidermis, where waxes are synthesized, while subcellular localization showed that CsWAX2 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
95
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(100 citation statements)
references
References 65 publications
4
95
0
1
Order By: Relevance
“…In comparison to the WT, the CsWAX2 transgenic cucumber plants showed significant improvement in resistance to drought and pathogens. These results suggested that CsWAX2 plays an important role in the biosynthesis of wax, influencing the response to biotic and abiotic stresses in cucumber (Wang et al, 2015). Karaba (2007) transferred AtCER1 , AtCER6 and AtWAX2 , which are involved in the pathways of wax biosynthesis, into tomato and the transformed tomato lines exhibited enhanced epicuticular wax predominantly consisted of alkanes.…”
Section: Biosynthesis Of Plant Cuticular Wax In Drought Stress Tolerancementioning
confidence: 93%
See 1 more Smart Citation
“…In comparison to the WT, the CsWAX2 transgenic cucumber plants showed significant improvement in resistance to drought and pathogens. These results suggested that CsWAX2 plays an important role in the biosynthesis of wax, influencing the response to biotic and abiotic stresses in cucumber (Wang et al, 2015). Karaba (2007) transferred AtCER1 , AtCER6 and AtWAX2 , which are involved in the pathways of wax biosynthesis, into tomato and the transformed tomato lines exhibited enhanced epicuticular wax predominantly consisted of alkanes.…”
Section: Biosynthesis Of Plant Cuticular Wax In Drought Stress Tolerancementioning
confidence: 93%
“…AtACBP1 is mainly involved in the secretion of lipid components and stem cuticle formation (Xue et al, 2014). Some studies have shown that a number of proteins, which are encoded by the genes responsible for cuticular wax biosynthesis such as AtCER1 , AtCER4 , AtWAX2, At5g02890, TaFAR1, OsWS1 and CsWAX2 , were found to be localized on the ER (Kamigaki et al, 2009; Wang et al, 2015, 2016; Xia et al, 2015; Xu et al, 2017). These results showed that the ER is an important site for the synthesis of cuticular wax in plants.…”
Section: Cuticular Wax Biosynthesis and Transportmentioning
confidence: 99%
“…It has been previously reported that mutations in wax biosynthesis causing glossy surface in Arabidopsis leaf and stem show reduced density of wax crystals and sometimes also alterations in the crystal shape and size (Jenks et al ., 1996). Similar results has been obtained in studies on surfaces of glossy fruits of orange (Liu et al ., 2012; 2015) and cucumber (Wang et al ., 2015a,b). Our study also demonstrated a decrease in the density of epicuticular wax crystal structures in GT fruit compared to WT fruit.…”
Section: Discussionmentioning
confidence: 99%
“…There are only few studies of wax biosynthesis in fruits and the studies have mostly focused on horticultural plants, such as tomato ( Solanum lycopersicum L., Mintz-Oron et al ., 2008), sweet cherry ( Prunus avium L., Alkio et al ., 2012), apple ( Malus domestica L., Albert et al ., 2013), orange ( Citrus sinensis L., Liu et al ., 2015; Wang et al ., 2016), mango ( Mangifera indica L., Tafolla-Arellano et al ., 2017), and cucumber ( Cucumis sativus L., Wang et al ., 2015a,b; Wang et al ., 2018). Bilberries ( Vaccinium myrtillus L.) are deciduous shrubs with wide distribution in cool temperate regions and mountain areas of Europe and Asia.…”
Section: Introductionmentioning
confidence: 99%
“…Alkenes had not been reported as constituents of Arabidopsis wax mixtures before, possibly because they are most apparent in leaf trichome wax and on young leaves, and present only as a minor compound class on mature leaves. It should be noted that alkenes had previously been identified in the cuticular waxes of cucumber fruits and stems, barley leaves and tomato fruits, and they were also found in maize pollen lipids and olive oil (Bianchi et al 1990;Bortolomeazzi et al 2001;Von Wettstein-Knowles 2007;Leide 2008;Wang et al 2015).…”
Section: Cell-type-specific Function Of Kcs16mentioning
confidence: 96%